Prioritization of putatively detrimental variants in euploid miscarriages - Buonaiuto, Silvia; Biase, Immacolata Di; Aleotti, Valentina; Ravaei, Amin; Marino, Adriano De; Damaggio, Gianluca; Chierici, Marco; Pulijala, Madhuri; D’Ambrosio, Palmira; Esposito, Gabriella; Ayub, Qasim; Furlanello, Cesare; et al. (Scientific reports, 2022)
Miscarriage is the spontaneous termination of a pregnancy before 24 weeks of gestation. We studied the genome of euploid miscarried embryos from mothers in the range of healthy adult individuals to understand genetic susceptibility to miscarriage not caused by chromosomal aneuploidies. We developed gp , a pipeline that we used to prioritize 439 unique variants in 399 genes, including genes known to be associated with miscarriages. Among the prioritized genes we found STAG2 coding for the cohesin complex subunit, for which inactivation in mouse is lethal, and TLE4 a target of Notch and Wnt, physically interacting with a region on chromosome 9 associated to miscarriages.